(untitled) (Journal of Building and Road Research, 2021)
Experimental model tests were carried out to study the bearing capacity of footings on stiff clay overlying very loose sand. Emphasis was given to the effects of the thickness of the clay (H) relative to the footing size (D). The clay thickness was fixed during the experiments and the foundation was represented by rigid circular steel plates of different sizes to give H/D ratios ranging from 0.6 to 2.0. The shear parameters of the two soils were measured in the laboratory at their placement conditions. The load tests were carried out to failure. The load settlement curves showed non-linear relationship. The ultimate bearing capacity decreased with increasing plate diameter. For the same plate (150mm) the bearing capacity on homogeneous stiff clay is more than twice that of the stiff clay overlying loose sand. The bearing capacity factor Nc was back-calculated from the results of the model tests. The very loose sand caused the factor to decrease to values less than 3.0 for H/D smaller than 1.0. The effective depth which is the smallest thickness of the stiff clay that does not allow the lower layer to affect bearing capacity is greater than twice the plate diameter (> 2D).